Analisis Yuridis Keabsahan Perjanjian Jual Beli Tanah Dengan Dasar Tipu Muslihat (Niet Zoude Aangegaan) (Studi Putusan Nomor 113/Pdt.G/2019/PN.Mjk) - Yudha, Erlangga Wira; Yulianingsih, Wiwin (Universitas Gorontalo, 2025)
This research discusses the validity of a land sale and purchase agreement allegedly made on the basis of deception (niet zoude aangegaan), using a case study of Decision Number 113/Pdt.G/2019/PN.Mjk. This research uses a normative legal method with a statutory approach, case approach, and conceptual approach. The data used in this research is secondary data obtained from literature studies and interviews. The results show that there are complex legal relationships between the parties, including debt and credit relationships, land certificate lending, and buying and selling of land. Although this legal relationship is regulated in accordance with the applicable provisions, there are indications of the use of false identity by the buyer in the Deed of Sale and Purchase No. 85/2017. This deed, which was made by a notary, allegedly violates the subjective requirement for the validity of an agreement, namely an agreement arising from fraud. As a result of this fraud, the deed can be canceled through a court process because it does not meet the validity requirements of the agreement as stipulated in Article 1320 of the Civil Code. This research highlights the importance of honesty in making agreements, especially in land sale and purchase transactions, to avoid legal disputes that harm the parties involved.